(untitled) (Conference Zone, 2022)
Linguistics today pays great attention to the differences between Uzbek and English etiquette. The method of comparative studies is specifically important. This article offers an outline of etiquette after which compares the differences between Uzbek and English etiquette. The peculiarities of translation pragmatics in the interpretation from Uzbek to English are defined in the instance of translation into Uzbek.